Critical Success Factors for Safety Management of High-Rise Building Construction Projects in China - Yadi Li; Yan Ning; Wei Tong Chen (Advances in Civil Engineering)
This study aims at identifying the critical success factors (CSFs) for safety management of high-rise building construction projects and exploring interactions among such CSFs. Study data were sourced from semistructured interviews and a questionnaire survey administered in China. The study constructs a third-order CSFs system containing six CSFs: management measures, management organization, technical and management plan, worker safety behavior, safety environment, and worker safety quality. Among these, management organization is found to be the key factor affecting construction safety management performance, while worker safety behavior is a factor with a direct impact. Implications for practice are proposed. This study enriches the existing literature on the CSFs and performance evaluation of construction safety management in high-rise building construction projects. Safety performance of high-rise building construction projects can be effectively enhanced by improving the professional competence of safety management organizations.